The Relationship Between Digital Literacy and Students’ Science Process Skills in Junior High Schools - Darmaji; Astalini; Nursulistiyo, Eko; Kurniawan, Dwi Agus; Husna, Sri Muslimatul; Perdana, Rahmat (LPPM Undiksha, 2023)
Science process skills are one of the skills that can develop potential in students. Science process skills refer to cognitive and psychomotor aspects, so as to create a meaningful learning based on student experience. Digital literacy abilities and students' science process skills are rarely considered in the learning process, so an analysis is needed to determine students' digital literacy skills and science process skills. This study aims to analyze the relationship between digital literacy skills and science process skills in simple plane materials. The research method used is a mixed method with an explanatory design. The research subjects used were 24 students. The research instruments were digital literacy questionnaires, science process skills observation sheets, and interview sheets. Data analysis techniques used quantitative data analysis and qualitative data analysis. The results of the Pearson correlation test showed that there was a significant relationship between digital literacy skills and students' science process skills in simple plane material. The researcher hopes that further research can determine the relationship based on gender.